Improving Students' Mathematics Learning Outcomes Through the Cooperative Learning Webbed Model at the Second Grade of SMP Negeri 3 Kolaka - Andi Mariani Ramlan; Irfan Irfan; Fitriyani Hali (Universitas Sembilanbelas November Kolaka, 2020)
This study aims to improve the mathematics learning outcomes of class VIIB students of SMP Negeri 3 Kolaka through the Webbed type of cooperative learning model. This type of research is classroom action research with research procedures covering planning, implementing actions, observing and reflecting. The implementation of the action consists of 2 cycles. Each cycle is carried out in accordance with the changes to be achieved and adjusted to the factors being investigated. Sources of research data are teachers and students of class VIIB, totaling 25 students. The types of data obtained are quantitative data obtained from learning outcomes tests and qualitative data obtained through observation sheets. The results of the study refer to the Minimum Completeness Criteria (KKM), namely at least 80% of students have obtained a minimum score of 70. From the results of the evaluation of the first cycle of action, classical completeness achieved is 63.6% (14 students from 25 students) who get a score of 70 with an average value of 68.4. From the results of the second cycle test evaluation, classical completeness was obtained as much as 86.4% (19 students from 25 students) obtained a score of 70 with an average value of 78.2. The implementation of the second cycle of action gave an increase of 22.8% from the first cycle evaluation test. So it was concluded that the mathematics learning outcomes of class VIIB students of SMP Negeri 3 Kolaka could be improved through the webbed type of cooperative learning model.